Tinjauan Atas Prosedur Audit Kas dan Setara Kas Pada Kantor Akuntan Publik di Makassar - Masnawaty Sangkala (Journal of Economic Education and Entrepreneurship Studies, 2022)
This study aims to determine the cash and cash equivalent audit procedures at KAP Masnawaty Sangkala, SE., M.Si., Ph.D., Ak., CA., CPA in Makassar. The variable that is the focus of this research is the Cash and Cash Equivalent Audit procedures at KAP Masnawaty Sangkala, SE., M.Si., Ph.D., Ak., CA., CPA in Makassar. The data collection method used is documentation. The data analysis was carried out using descriptive analysis. The results of this study indicate that the cash and cash equivalent audit procedures at KAP Masnawaty Sangkala, SE., M.Si., Ph.D., Ak., CA., CPA in Makassar are in accordance with the theory proposed by Sukrisno Agoes.